Evaluation of the Information Content of YoutubeTM Videos in Turkish on Botulinum Toxin Injection Administered to the Masseter Muscle in the Treatment of Bruxism: A Cross-Sectional Study: Bruxism and Botox on Youtube - Sefa Çolak; Aras Erdil; Mustafa Sami Demirsoy (Atatürk University, 2024)
Objective:The study aims the evaluation the content on the YouTubeTM platform about botulinum toxin injection for the treatment of bruxism regarding information quality.Methods: The YoutubeTM database was scanned using the keyword "masseter botox." According to the study criteria, 33 videos were included and the number of views, likes, dislikes, comments, duration, and the number of days since uploading were recorded. According to their quality, the information content was divided into four groups (bad, poor, good, excellent). Shapiro-Wilk, Kruskal-Wallis, and post-hoc Tamhane-T2 tests were used to analyze the study data, and Fleiss Kappa analysis was used to evaluate the agreement between researchers. Statistical significance was determined as p<0.05.Results: According to the installer source, 19 videos were uploaded by doctors, seven by patients, five by doctors+patients, and two by other sources. Significant differences were obtained between the uploaded source and the duration of the video; the number of views, the number of likes, dislikes, comments, interaction index, and viewing rate were respectively p<0.001, p=0.035, p=0.003, p=0.008, p=0.002, p=0.007, and p=0.013. According to the information content, 14 videos were bad, 15 were poor, and four had good information. A significant difference was observed between the number of comments (p=0.016) and video duration (p=0.029) regarding the information content quality.Conclusion: The results have indicated that YouTubeTM content cannot be a reliable source of information. Experts should recommend videos that meet specific standards to patients and produce content that provides accurate information in the absence of this content.